Geospatial analysis of neighborhood deprivation index (NDI) for the United States by county. Issue 1 (1st January 2020) - Andrews, Marcus R.; Tamura, Kosuke; Claudel, Sophie E.; Xu, Samantha; Ceasar, Joniqua N.; Collins, Billy S.; Langerman, Steven; Mitchell, Valerie M.; Baumer, Yvonne; Powell-Wiley, Tiffany M.
ABSTRACT: Little is known about the spatial clustering of neighborhood deprivation across the United States (US). Using data from the 2010 US Census Bureau, we created a neighborhood deprivation index (NDI: higher NDI indicates higher deprivation/ lower neighborhood socioeconomic status) for each county within the US County level scores were loaded into ArcGIS 10.5.1 where they were mapped and analyzed using Moran's I and Anselin Local Moran's I. Ultimately, NDI varies spatially across the US. The highest NDI scores were found in the Southeastern and Southwestern US states, and inland regions of Southern California. This information is critical for public health initiative development as planners may need to tailor the scale of their efforts based on the higher NDI neighborhoods of the county or geographic region with potentially greater chronic disease burden.